Study On Harnessing Solar Energy For Power Supply From Chancellor Complex Roof - Nurul Syahirah Binti Abdul Hamid, Nurul Syahirah (Universiti Teknologi Petronas, 2010)
Solar energy is one of renewable energy that is increasingly attracting consumers nowadays. It is a source of energy that is available to mankind on this planet. Unfortunately, not many of human being is aware with this amazing energy. However as the new technology is becoming more high –tech and more design of solar technology is created, people are more interested in knowing the capabilities of this energy. The constraint of this energy is most probably is the cost of installation of the solar system.